2016
DOI: 10.1353/hpu.2016.0093
|View full text |Cite
|
Sign up to set email alerts
|

Post-traumatic Stress Disorder Symptoms and Mental Health over Time among Low-Income Women at Increased Risk of HIV in the U.S.

Abstract: Women living in poverty suffer more post-traumatic stress disorder (PTSD) symptoms than do members of the general population; however we know little about factors associated with changes in their PTSD symptoms over time. Using data from HPTN 064, a cohort of women from low-income, high-HIV-prevalence communities across six eastern states (n=1,860), we assessed the prevalence of and changes in PTSD symptoms over 12 months and the effect of potential predictors on symptom acquisition and remission (via the Prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 59 publications
(79 reference statements)
1
19
0
Order By: Relevance
“…Among domiciled samples, food insecurity has been associated with negative physical health outcomes, including obesity (Hernandez et al, 2017), hypertension (Venci and Lee, 2018; Wang et al, 2015) and diabetes (Venci and Lee, 2018; Wang et al, 2015). Food insecurity has also been associated with depression (Wang et al, 2015; Weiser et al, 2011; Whitaker et al, 2006) and post-traumatic stress disorder (PTSD) (Golin et al, 2016; Mugisha et al, 2015). While the research on food insecurity and health outcomes is scarce among homeless adults, several studies have found a positive association between food insecurity and mental health problems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among domiciled samples, food insecurity has been associated with negative physical health outcomes, including obesity (Hernandez et al, 2017), hypertension (Venci and Lee, 2018; Wang et al, 2015) and diabetes (Venci and Lee, 2018; Wang et al, 2015). Food insecurity has also been associated with depression (Wang et al, 2015; Weiser et al, 2011; Whitaker et al, 2006) and post-traumatic stress disorder (PTSD) (Golin et al, 2016; Mugisha et al, 2015). While the research on food insecurity and health outcomes is scarce among homeless adults, several studies have found a positive association between food insecurity and mental health problems.…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence of associations between food insecurity and poor health, depression, and PTSD among domiciled adults (Golin et al, 2016; Hernandez et al, 2017; Wang et al, 2015). However, there is scant evidence for such a relationship for adults experiencing homelessness even though they are disproportionately affected by food insecurity (Martin-Fernandez et al, 2018; Palar et al, 2015; Whitbeck et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…This finding is similar to reports in the community of men who have sex with men (MSM), where race has been shown to be a strong predictor of risk even though reported behaviours are similar among the groups 13 14 15 . Additionally, syndemic factors such as poverty, trauma, substance abuse, homelessness and incarceration as well as San Diego’s border location likely contribute to the high prevalence of undiagnosed infection among Hispanic women 16 17 18 19 20 21 22 23 24 25 26 . Similarly, the HPTN 064 study, which aimed to estimate the overall new HIV infection rate in women at risk for HIV in the United States, study subjects perceived their risk as due to structural and contextual factors 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Cluster 4: Health-care system for infectious diseases For HIV/AIDS, tuberculosis, and other diseases, limited access to mental health care (Cluster 3) has caused an increasing number of people to live with mental illness [95,96]. Contemporary research has highlighted the identification of risk factors [96]; mental health care has been integrated into HIV programs for many years [97,98]. However, current political, socioeconomic, and cultural factors still affect the adoption, assimilation, and elimination of depression among those suffering from infectious diseases.…”
Section: Cluster 3: Primary Health Care and Mental Healthmentioning
confidence: 99%